ANALYSIS OF THE IMPACT OF E-COMMERCE USE ON THE CONSUMER LIFESTYLE OF GEN Z: A STUDY BASED ON ISLAMIC ECONOMIC VALUES - Pradana, Muh. Rizqi Virgiawan (Universitas Suryakancana, 2025)
This research aims to analyze the impact of the use of E-Commerce on consumer lifestyles among Generation Z from an Islamic economic perspective. The research method uses a qualitative approach by collecting data through in-depth interviews and literature studies. Interviews were conducted with Generation Z students at UIN K.H. Abdurrahman Wahid Pekalongan, while secondary data was obtained from various related literature. The research results show that ease of access, promotions and exposure to social media are the main factors that trigger consumer behavior among Generation Z when using E-Commerce platforms. The influence of social media that displays luxurious lifestyles also encourages impulsive consumption behavior. In an Islamic economic perspective, this behavior is contrary to the principles of simplicity and balance. To overcome the negative impacts, it is necessary to increase sharia-based financial literacy and educate about the principles of sustainable consumption. It is hoped that this strategy can form wiser consumption patterns that are in line with Islamic values.